FAKTOR FAKTOR PENGHAMBAT PENGELOLAHAN SAMPAH YANG BERADA DI PASAR OEBA KOTA KUPANG NUSA TENGGARA TIMUR - Arman, Yohanes; Rabe, Mariana Bunga; Pahawu, Rizky Semelweys Bastian (Gapenas Publisher, 2025)
Waste management at Oeba Market, Kupang City, East Nusa Tenggara (NTT), faces various challenges that can hinder the effectiveness of the optimal waste management process. Oeba Market is one of the main trading centers in Kupang City which produces quite a large volume of waste every day, both from the activities of traders and visitors. Although various management efforts have been made by the government and the community, there are still a number of factors that hinder the creation of an efficient and sustainable waste management system. This study aims to identify factors that hinder waste management at Oeba Market and analyze their impact on the cleanliness and health of the market environment. The research method used is normative legal research with a statutory approach. The sources of materials used include primary legal materials in the form of laws and regulations and secondary legal materials in the form of legal journals and the internet. The results of the study indicate that there are several main factors that hinder waste management at Oeba Market. These factors include low public awareness, both traders and visitors, regarding the importance of waste sorting and management, lack of human resources, limited supporting facilities such as separate trash bins for organic and non-organic waste, and a minimal number of cleaning staff which have an impact on the suboptimal waste management. In addition, the budget allocated for waste management is still very limited, and coordination between local governments, market managers, and the community regarding waste management at Oeba Market is still ineffective. The recommendations from this study emphasize the importance of increasing public awareness through more intensive education regarding waste sorting. In addition, it is necessary to provide adequate waste management facilities, as well as increase budget allocation and resources to support more effective waste management at Oeba Market. The active role of the government and related parties is also very much needed in strengthening coordination to achieve better waste management